1996
DOI: 10.1016/0375-9474(96)00033-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of nucleon structure in finite nuclei

Abstract: The quark-meson coupling model, based on a mean field description of non-overlapping nucleon bags bound by the self-consistent exchange of $\sigma$, $\omega$ and $\rho$ mesons, is extended to investigate the properties of finite nuclei. Using the Born-Oppenheimer approximation to describe the interacting quark-meson system, we derive the effective equation of motion for the nucleon, as well as the self-consistent equations for the meson mean fields. The model is first applied to nuclear matter, after which we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
544
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(552 citation statements)
references
References 64 publications
5
544
0
Order By: Relevance
“…It is found that the magnitude of the σ field decreases as the hadronic density increases, in accordance with the corresponding tendency for chiral symmetry restoration. This mechanism has a similar effect, for saturation, as the analogous one proposed by Guichon [14], according to which confinement is affected by an increase of the density in such a way as to become gradually less effective, which amounts to an increasing repulsion. For nuclear matter, the NJL model leads to binding but the binding energy per particle does not have a minimum except at a rather high density where the nucleon mass is small or vanishing.…”
Section: Extended Njl Modelsupporting
confidence: 57%
See 2 more Smart Citations
“…It is found that the magnitude of the σ field decreases as the hadronic density increases, in accordance with the corresponding tendency for chiral symmetry restoration. This mechanism has a similar effect, for saturation, as the analogous one proposed by Guichon [14], according to which confinement is affected by an increase of the density in such a way as to become gradually less effective, which amounts to an increasing repulsion. For nuclear matter, the NJL model leads to binding but the binding energy per particle does not have a minimum except at a rather high density where the nucleon mass is small or vanishing.…”
Section: Extended Njl Modelsupporting
confidence: 57%
“…In Fig. 4 we compare EOSI with two different parametrizations of the non-linear Walecka model, NL3 [16] and TM1 [22], and the quark meson coupling model (QMC) [14] for symmetric matter. In QMC the structure of nucleons is taken into account having as underlying model the MIT Bag model.…”
Section: Isospin Asymmetric Nuclear Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…The QMC model, which describes nuclear matter based on the quark degrees of freedom, was introduced using MIT bag model by Guichon [23], and Frederico et al [24] with a confining harmonic potential. The model was successfully applied for finite nuclei [25], and also mesons properties in medium [26]. In the QMC model, because of the surrounding medium, the bound state mesons and baryons are modified, compared with those in vacuum.…”
Section: Rho-meson In-mediummentioning
confidence: 99%
“…In nuclear matter, the scalar polarizability is the only effect of the internal structure in mean-field approximation. On the other hand, in finite nuclei, the variation of the vector field across the hadronic volume also leads to a spin-orbit term in the nucleon energy [27].…”
Section: Qmc Modelmentioning
confidence: 99%